Empowering Rural Women: Analyzing Awareness and Usage of Fintech Tools in Shivamogga District - Mrs Divya S.P,,; Dr Subhadra P.S,, (The Bioscan, 2024)
This study examines the awareness and adoption levels of fintech tools among rural women in Shivamogga district, Karnataka, India. Fintech solutions have the potential to empower women by providing them access to affordable and efficient financial services, yet their adoption remains limited in rural areas. Through a combination of primary data collection and secondary analysis, the research identifies digital literacy, socio-cultural norms, and infrastructural challenges as key barriers to adoption. The findings also highlight the role of financial education programs, government initiatives, and community-based organizations in fostering fintech usage. This study provides actionable insights for policymakers, fintech developers, and stakeholders to enhance financial inclusion and economic empowerment among rural women. The study uses an analytical research design. Conveniently, a questionnaire was distributed to the 50 women in the sample size who were fintech users in rural Karnataka’s Malnad Region. The data were rated using a five-point Rensis Likert scale. The Percentage Analysis, Mean-value analysis and Correlation Analysis have been employed for statistical analysis using Excel According to the report, the majority of respondents used fintech services because they were simple to use.